Effects of connectivity between aquatic environments in the fi sh community structure in coastal lagoons of the Restinga of Jurubatiba National Park, Rio de Janeiro State, Brazil - Botero, Jorge Iván Sánchez; Garcez, Danielle Sequeira; Caramaschi, Erica Pellegrini (Arquivos de Ciências do Mar, 2009)
Fish community attributes (composition, diversity, richness, abundance and biomass) were compared between Cabiúnas, Comprida, Carapebus, Paulista and Preta coastal lagoons located at Restinga of Jurubatiba National Park (RJ), during periods of connectivity to adjacent habitats, appraised by variations in salinity and rainfall. Changes in the structure of the ichthyofauna in this environment were not signifi cant. This fact is related to the homogeneity in the mean pluviosity during the dry and rainy season periods studied that kept connectivity with freshwater environments (pools, channels, marshes and streams) thus preventing disconnectivity. However, the low presence of marine species in the lagoons indicated little infl uence of swells on the salinity variation, as well as in the entrance of marine fi shes into those environments. With the results it is suggested that the scarce variation in the ichthyofauna structure in the fi ve lagoons is related to the connectivity to adjacent freshwater environments due to intensive rainfall during the studied period. It is also possible to conclude that, although the historical reports show relatively high frequencies of moderate and strong overtopping of the sea, these were not suffi cient to modify the community structures in the above-mentioned lagoons.